2022
DOI: 10.3390/nano12173080
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of Factors Affecting the Synthesis of SiO2@Au for the Enhancement of Raman Spectroscopy

Abstract: The reaction time, temperature, ratio of precursors, and concentration of sodium citrate are known as the main factors that affect the direct synthesis process of SiO2@Au based on the chemical reaction of HAuCl4 and sodium citrate. Hence, we investigated, in detail, and observed that these factors played a crucial role in determining the shape and size of synthesized nanoparticles. The significant enhancement of the SERS signal corresponding to the fabrication conditions is an existing challenge. Our study res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The peaks at 1376 cm −1 (D) and 1556 cm −1 (G) show that silicon oxide nanoparticles are not reduced. The weak band at 1090 cm −1 is also present indicating the presence of silicon oxide [99–103] . Raman spectra for Ge oxide nanoparticles shows the presence and crystalline nature of Ge oxide nanoparticles.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The peaks at 1376 cm −1 (D) and 1556 cm −1 (G) show that silicon oxide nanoparticles are not reduced. The weak band at 1090 cm −1 is also present indicating the presence of silicon oxide [99–103] . Raman spectra for Ge oxide nanoparticles shows the presence and crystalline nature of Ge oxide nanoparticles.…”
Section: Resultsmentioning
confidence: 96%
“…The weak band at 1090 cm À 1 is also present indicating the presence of silicon oxide. [99][100][101][102][103] Raman spectra for Ge oxide nanoparticles shows the presence and crystalline nature of Ge oxide nanoparticles. The band at 575 cm À 1 is Raman actives modes (first order and second order) transverse optical phonon modes (TO and 2TO) are present which are TO modes of crystalline Ge.…”
Section: Resultsmentioning
confidence: 99%
“…The SPR peak of the Au–Pt/Mn 3 O 4 , Au–Pt/Mn 2 O 3 , and Au–Pt/AC catalysts is gradually red-shifted compared to Au–Pt/Mn x O y C z catalysts. According to Thao et al, the SPR peak is red-shifted when the particle diameter is increased. It is confirmed that Mn x O y C z has a better size limitation effect.…”
Section: Resultsmentioning
confidence: 96%